High-harmonic generation in CdTe with ultra-low pump intensity and high photon flux - Long, Zhe (2023)
An ultra-low pump intensity and high photon flux have been long pursuits of high harmonic generation (HHG) in solids. However, there is lack of a criterion to identify a pristine solid material exhibiting such characteristics. Here, we report systematic investigation into HHG from a cadmium telluride (CdTe) bulk crystal with a flat band dispersion near the Fermi level which leads to a large density of states. The measured pump intensity for the 31st harmonics (229 nm) is only 75 GW/cm2, one order of magnitude lower than that of other pristine crystals including two-dimensional materials reported so far. A comparative measurement shows CdTe has two-to-three orders of magnitude stronger HHG than silicon does, and high HHG yields in the ultraviolet region compared to GaSe. A high photon flux of ~ 6 × 1012 photons/s (5th −8th) with a robust long-time sustainability is obtained. This work offers a route towards compact vacuum ultraviolet laser sources.